Using Genetic and Phenotypic Comparisons to Evaluate Apparent Segregation among Kokanee Spawning Groups. Issue 1 (26th February 2018) - Whitlock, Steven L.; Campbell, Matthew R.; Quist, Michael C.; Dux, Andrew M.
Abstract: Genetic and phenotypic traits of spatially and temporally segregated kokanee Oncorhynchus nerka spawning groups in Lake Pend Oreille, Idaho, were compared to test for evidence of divergence on the basis of ecotype (stream spawners versus shoreline spawners) and spawn timing and to describe morphological, life history, and reproductive variation within and among groups. Early and late spawning runs were found to be reproductively isolated; however, there was no clear evidence of genetic differentiation between ecotypes. Spawning groups within the same ecotype differed in length, age distribution, mean length at age, fecundity, and egg size. Variation in reproductive attributes was due primarily to differences in length distributions. Larger‐bodied shore‐spawning kokanee were located in areas where egg survival is known to be enhanced by downwelling, suggesting that the distribution of shore‐spawning kokanee may be partly structured by competition for spawning habitats with groundwater influence. This study contributes to other research indicating that introduced kokanee populations are unlikely to undergo adaptive divergence if they have a history of population fluctuations and are supplemented regularly.